If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -5) + -1 = -3(-7x + 7) + -6y Reorder the terms: 5(-5 + x) + -1 = -3(-7x + 7) + -6y (-5 * 5 + x * 5) + -1 = -3(-7x + 7) + -6y (-25 + 5x) + -1 = -3(-7x + 7) + -6y Reorder the terms: -25 + -1 + 5x = -3(-7x + 7) + -6y Combine like terms: -25 + -1 = -26 -26 + 5x = -3(-7x + 7) + -6y Reorder the terms: -26 + 5x = -3(7 + -7x) + -6y -26 + 5x = (7 * -3 + -7x * -3) + -6y -26 + 5x = (-21 + 21x) + -6y Solving -26 + 5x = -21 + 21x + -6y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21x' to each side of the equation. -26 + 5x + -21x = -21 + 21x + -21x + -6y Combine like terms: 5x + -21x = -16x -26 + -16x = -21 + 21x + -21x + -6y Combine like terms: 21x + -21x = 0 -26 + -16x = -21 + 0 + -6y -26 + -16x = -21 + -6y Add '26' to each side of the equation. -26 + 26 + -16x = -21 + 26 + -6y Combine like terms: -26 + 26 = 0 0 + -16x = -21 + 26 + -6y -16x = -21 + 26 + -6y Combine like terms: -21 + 26 = 5 -16x = 5 + -6y Divide each side by '-16'. x = -0.3125 + 0.375y Simplifying x = -0.3125 + 0.375y
| 2n-8=-54 | | -3-3(2m-6)=3(m+1)-5m | | 3=-5-4x | | 6=2-7x | | 10xy+16x^3=15xy^3+3x+7x^2 | | 24(2x-1)=8(x+2) | | k+8.3=10.8 | | 3x+5-5x+5=6x+7 | | 6(4+v)+35v=12v | | f(2)=x^2-2 | | 7+6(n-5)=7+3(7n+5) | | 3(x+0.75)+2(x+1.50)= | | (-x)(-y)(2-3z)=0 | | 18+(9-3)*3=x | | -3-3(2n-6)=3(m+1)-5m | | 4x+(2x+12)=180 | | 4x^3+2x-8=0 | | 7w-3=39 | | 2cosx/sinx | | .98+4.83=f+4.35f | | 2y+13=49 | | -3(4+3x)=6 | | x+4x+5x=14 | | 3/5x6/7 | | W=5/12=1/2 | | 6x+8=-2x-8 | | 6(3+2m)=(-18) | | 4(w-5)=5(3+w) | | 90+11x+7x=180 | | 3g-2=3g+9 | | 12h-7=-9h-26 | | 2c-3= |